2019
DOI: 10.1002/cjoc.201900245
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport through Peptides in Single‐Molecule Electrical Measurements

Abstract: Charge transport across the peptide chains is one of the vital processes in the biological systems, so understanding their charge transport properties is an indispensable prerequisite to explain the complex biochemical phenomenon. Here, we review the charge transport mechanism, the influence of the special groups and the experimental conditions on the charge transport through the peptide backbone by employing the single-molecule electrical measurements. Besides, we further review the recent progresses in charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 98 publications
(78 reference statements)
0
14
0
1
Order By: Relevance
“…Intermolecular charge transport in π-stacked aromatic groups is central to organic electronics and biological processes . In the field of organic electronics, it is widely believed that device efficiency critically depends on interchain charge transport between π-conjugated molecules. In biology, charge transport through π-stacked DNA base pairs , and aromatic amino acid residues , plays a key role in metabolism, photosynthesis, and oxidative damage and repair of DNA . From this view, understanding intermolecular charge transport through π-stacked molecules is essential for elucidating the fundamental mechanisms behind biological redox processes and for designing new materials for organic electronics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intermolecular charge transport in π-stacked aromatic groups is central to organic electronics and biological processes . In the field of organic electronics, it is widely believed that device efficiency critically depends on interchain charge transport between π-conjugated molecules. In biology, charge transport through π-stacked DNA base pairs , and aromatic amino acid residues , plays a key role in metabolism, photosynthesis, and oxidative damage and repair of DNA . From this view, understanding intermolecular charge transport through π-stacked molecules is essential for elucidating the fundamental mechanisms behind biological redox processes and for designing new materials for organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, this conclusion was challenged in a subsequent publication in which the formation of 2:2 quaternary complexes between arylviologen and CB [8] was reported. 59 To understand how the synthetic host affects the charge transport properties of stacked pyridinium, we use cucurbit [7]uril (CB [7]), a smaller homologue to CB [8] (Figure 4a−b). CB [7] shows similar binding properties to CB [8] albeit with a smaller portal diameter (5.4 Å) compared to CB[8] (6.9 Å), which allows for the complexation of only one aromatic guest molecule (Figures S48−S55).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conductance of single peptides was measured in a mechanically controlled break junction (MCBJ) at fixed distance for recognition purposes 15 and in the STM-BJ as a function of electrode separation. [16][17][18] In the later experiments, the weak effect of the amino-acid composition on the peptide conductance was confirmed. Typically, the analysis only involves the study of the most prominent conductance peak and stretched peptide chains were found to be poor conductors.…”
Section: Introductionmentioning
confidence: 67%